Managing a Mandibular Second Premolar with Three-Canal and Taurodontism: A Case Report - Mokhtari, Hadi (Iranian Center for Endodontic Research, 2013)
Root canal anatomy diversity and aberrations are common especially in permanent dentition. A thorough understanding of the basic root canal anatomy and its diversities are necessary for successful endodontic treatment. Mandibular second premolars are usually single-rooted and have one root canal. Incidence of three separate root canals in this tooth is quite rare and taurodontism with three separate canals has never been reported in literature so far. The use of cone-beam computed tomography scan in this rare case greatly contributed to making a confirmatory diagnosis and successful nonsurgical endodontic management thereafter.